1999
DOI: 10.1063/1.166451
|View full text |Cite
|
Sign up to set email alerts
|

Optimal chaos control through reinforcement learning

Abstract: A general purpose chaos control algorithm based on reinforcement learning is introduced and applied to the stabilization of unstable periodic orbits in various chaotic systems and to the targeting problem. The algorithm does not require any information about the dynamical system nor about the location of periodic orbits. Numerical tests demonstrate good and fast performance under noisy and nonstationary conditions. (c) 1999 American Institute of Physics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…While controlling chaotic systems through stabilisation of an unstable periodic orbit remains important method of chaos control [14], but as studied in [10] the method requires that each orbit be observed while waiting for particular type of orbit to occur. This further requires modification in input parameters through which the operating point on the attractor of the system can be shifted to a stable region to meet the desirable objective.…”
Section: Controlling a Chaotic Process By Altering Its Bifurcation DImentioning
confidence: 99%
See 1 more Smart Citation
“…While controlling chaotic systems through stabilisation of an unstable periodic orbit remains important method of chaos control [14], but as studied in [10] the method requires that each orbit be observed while waiting for particular type of orbit to occur. This further requires modification in input parameters through which the operating point on the attractor of the system can be shifted to a stable region to meet the desirable objective.…”
Section: Controlling a Chaotic Process By Altering Its Bifurcation DImentioning
confidence: 99%
“…While this approach leads to successful classification of slightly differing periodic data, its use in developing any controller has not been demonstrated. In [14] it has been shown that using reinforcement learning techniques, control of chaotic systems can be achieved from observed data based methods without formal models, but the approach has been limited to stabilising an unstable fixed orbit. Therefore, the proposition brought out in [10], where modelling the system through multiinput and multi-output recurrent neural networks, training it to very low MSE levels using back-propagation algorithm, to achieve a capability to predict number of subsequent steps, has been adopted here, for the study of real-world systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [8] we showed how a single logistic map can be controlled through a method based on reinforcement learning. Here we extend this method to the control of 1-D and 2-D LCML.…”
Section: The Control Algorithmmentioning
confidence: 99%
“…The use of reinforcement learning to control chaotic systems was first suggested by Der and Herrmann [7] who applied it to the logisitic map. In [8] we generalized the method and applied it to the control of several discrete and continous lowdimensional chaotic and hyperchaotic systems. Lin and Jou [9] proposed a reinforcement learning neural network for the control of chaos and applied it to the logistic and the Hénon map.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation